ANALISIS PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA (KUALITATIF DESKRIPTIF PADA KELAS IV SD DALAM PEMBELAJARAN BAHASA INDONESIA) - Anggraenita, Windi; Rizki Hadiwijaya Z; Geri Syahril Sidik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the crucial role of teachers in enhancing students’ learning motivation, particularly in Indonesian language instruction at the elementary level. The research aims to analyze how teachers foster motivation among fourth-grade students at SDN Sukarame. This study employs a descriptive qualitative design, involving 22 students and one classroom teacher as participants. Data were collected through observation, interviews, and questionnaires, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that teachers act as facilitators, motivators, and communicators in the learning process. A key finding is the use of reward strategies, where praise and simple incentives effectively increase students’ enthusiasm and participation. Approximately 81% of students demonstrated high to very high learning motivation, marked by improved activeness, confidence, and engagement in classroom activities. In conclusion, an appreciative and humanistic teaching approach significantly enhances students’ motivation to learn. This research contributes to the development of motivation-based teaching strategies in elementary education. It is recommended that teachers continue implementing reward-based and active learning approaches to create an engaging and enjoyable learning atmosphere. Keywords: teacher’s role, learning motivation, reward strategy, Indonesian language learning, qualitative descriptive.